Lives in the law - Douglas, Lawrence; Sarat, Austin; Umphrey, Martha Merrill (Ann Arbor : University of Michigan Press, 2002)
Examines how the lives of individuals, social groups, and nations are fashioned by their engagement with the law.
Theoretical perspectives on lives in the law : an introduction / Lawrence Douglas, Austin Sarat, and Martha Merrill Umphrey -- The Chicago conspiracy trial as a Jewish morality tale / Pnina Lahav -- Law and everyday death : infanticide and the backlash against woman's rights after the Civil War / Sarah Barringer Gordon -- Dependency by law : welfare and identity in the lives of poor women / Frank Munger -- Labor's subjects / Vicki Schultz -- France and trials for crimes against humanity / Annette Wieviorka.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Sociological jurisprudence; Law -- Social aspects -- United States; Sociologie juridique; Law -- Social aspects; Sociological jurisprudence; United States